Ambient Pressure Photoemission Spectroscopy Reveals the Mechanism of Carbon Soot Oxidation in Ceria‐Based Catalysts. Issue 17 (7th September 2016) - Soler, Lluís; Casanovas, Albert; Escudero, Carlos; Pérez‐Dieste, Virginia; Aneggi, Eleonora; Trovarelli, Alessandro; Llorca, Jordi
Abstract: The front cover artwork for Issue 17/2016 is a collaboration between the research groups of Prof. Jordi Llorca at Universitat Politècnica de Catalunya – BarcelonaTECH (Spain), Prof. Alessandro Trovarelli at Università di Udine (Italy), and CIRCE beamline scientists at ALBA Synchrotron Light Source (Spain). The image shows the two cooperative routes for soot oxidation identified by AP‐XPS at the surface/subsurface of ceria and ceria‐zirconia catalysts for removing soot from motor vehicle emissions. See the Communication itself athttp://dx.doi.org/10.1002/cctc.201600615 . Abstract : "A study of the surface/subsurface of the catalysts under working conditions" This and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research athttp://dx.doi.org/10.1002/cctc.201600615 .